Severidade de isolados de Macrophomina spp. de plantas daninhas a feijão-caupi - Silva Neto, Alfredo Nogueira da (2017)
The fungus Macrophomina phaseolina is a polyphagous phytopathogen, which attacks more than 600 species of plants, including weeds that can host it. Pega-pinto (Boerhavia diffusa L.) and bredo (Trianthema portulacastrum L.) are common weeds that occur in areas of feijão-caupi (Vigna unguiculata L.), in Rio Grande do Norte and Ceará. When infected by M. phaseolina, this culture causes gray stem rot, drastically reducing yield. Therefore, the present work aimed to verify the virulence of Macrophomina spp. obtained from pega-pinto and bredo. The experiments were conducted in Vegetation House of the Universidade Federal Rural do Semi-Árido (UFERSA), in Mossoró-RN. Two trials were carried out to evaluate the severity of 100 isolates of Macrophomina, not first to posteriori 50 isolates in the pega-pinto roots and, in the second, 50 isolates from roots of bredo. In both assays, a Macrophomina Feijão-caupi isolate was used. The experimental design was completely randomized, with five replicates. All 50 isolates of Macrophomina spp. caused gray stem rot symptoms in caupi and 64% these isolate showed a similar severity to the caupi isolate. In the bredo, 90% of the isolates caused the disease, however none of them presented severity equal to the caused by caupi isolates